1997
DOI: 10.4028/www.scientific.net/msf.248-249.135
|View full text |Cite
|
Sign up to set email alerts
|

Hardness Enhancement and Crosslinking Mechanisms in Polystyrene Irradiated with High Energy Ion-Beams

Abstract: In the past, radiation effects studies on polymers were mostly aimed at understanding polymerization mechanisms in radiation curing and synthesis, and radiation induced degradation mechanisms. However, little effort has been expended to improve mechanical properties of polymers, because radiation sources such as e-beams, y -rays, and ultraviolet light, which have been used frequently, produce either small improvement due to crosslinking or more often cause degradation due to scission. In recent work at ORNL, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 7 publications
5
24
0
1
Order By: Relevance
“…In agreement with observations of the effect of irradiation on polymers reported in the literature [23], [25], the effect of radiation on SU-8 could not be simply related to the TID or to the total non-ionizing dose. The left graph in Fig.…”
Section: B Su-8supporting
confidence: 80%
See 3 more Smart Citations
“…In agreement with observations of the effect of irradiation on polymers reported in the literature [23], [25], the effect of radiation on SU-8 could not be simply related to the TID or to the total non-ionizing dose. The left graph in Fig.…”
Section: B Su-8supporting
confidence: 80%
“…The LET describes the energy loss from the perspective of the particle, whereas the stopping power is a measure of the energy absorbed by the material. LET-dependent radiation effects, in which the observed damage is correlated to the electronic stopping power of the radiation, were investigated in various polymers including aromatic and aliphatic compounds [23], [25], [27], solid alanine [28], polystyrene, and polysilanes [29], [30]. However, [31] reported similar effects on the elongation to break in Ultem and Kapton irradiated by 3 MeV protons, 2 MeV electrons, or gamma-rays.…”
Section: Radiation-induced Degradation In Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…It is calculated by dividing the test force by surface area of contact, incorporating the plastic component of displacement. Results in this study showed that plasma treatment significantly increased surface microhardness, which could be attributed to the plasma-induced crosslinking phenomenon [36][37][38][39][40] . Thus, plasma would also be helpful in enhancing the etch resistance of denture bases 41) .…”
Section: Discussionmentioning
confidence: 87%